DETERMINING THE HUBBLE CONSTANT FROM HUBBLE PARAMETER MEASUREMENTS - Chen, Yun; Kumar, Suresh; Ratra, Bharat (The Astrophysical journal, 2017)
We use 28 measurements of the Hubble parameter, H(z), at intermediate redshifts to determine the present-day Hubble constant H0 in four cosmological models. We measure , and Mpc−1 (1 errors) in the ΛCDM (spatially flat and non-flat), CDM, and φCDM models, respectively. These measured H0 values are more consistent with the lower values determined from recent data on the cosmic microwave background and baryon acoustic oscillations, as well as with the value found from a median statistical analysis of Huchra's compilation of H0 measurements, but include the higher local measurements of H0 within the 2 confidence limits.